Educational Migration in Russian Regions: Statistical Approach - E. A. Pitukhin; O. A. Zyateva; L. V. Shchegoleva; V. E. Sokolov (Высшее образование в России)
Educational migration plays an important role in the implementation of admission plans for applicants to higher education institutions in a significant number of Russian regions. The aim of the work is to find out which regions are the most attractive for graduates in terms of higher education on the basis of the study of interregional migration of university entrants, as well as to identify the factors influencing the educational attractiveness of the regions. The research methodology is based on the statistical approach, which allows us to use publicly available data from official statistics. The information base of the study was the data of the federal statistical observation forms No. VPO-1, No. OO-1, as well as other official statistical data of the Federal State Statistics Service. The methods of the study included methods of comparative analysis and descriptive statistics, methods of data mining, such as analysis of key factors of influence and clustering. The main indicator of educational migration was selected as a statistical indicator – the share of students from the total enrollment who received a previous education in another subject of the Russian Federation. The analysis revealed ten factors that have the greatest influence on the indicator of educational migration. The clustering of 83 regions according to the space of selected characteristics resulted in five clusters with different values of the indicator of educational migration and different values of indicators of the quality of life. Three territorially different educational centers of gravity were identified: “Metropolitan”, “Southern” and “Siberian”, which include 27 regions of Russia from the two best clusters by the indicator of educational migration. The regions of the Arctic zone of the Northwestern Federal District and the Far East enjoy the least educational popularity. The trend has been revealed, which is a decrease in the value of the indicator of educational migration of most regions as they move away from the “metropolitan” educational center. The results of the study can be useful to the executive authorities of the regions when solving the tasks in the sphere of educational migration flows management.